2019
DOI: 10.1109/access.2019.2916717
|View full text |Cite
|
Sign up to set email alerts
|

Forensics and Deep Learning Mechanisms for Botnets in Internet of Things: A Survey of Challenges and Solutions

Abstract: The author N. Koroniotis would like to thank the Commonwealth's support, which is provided to the aforementioned researcher in the form of an Australian Government Research Training Program Scholarship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 84 publications
0
68
0
2
Order By: Relevance
“…Even though many forensic frameworks have been proposed [12,27,11], existing solutions for smart homes give emphasis on acquisition and neglect examination and analysis. Furthermore, no single framework has been acknowledged as superior, due to lack of standardization in IoT and heterogeneity of computer systems [28,29,3].…”
Section: Digital Forensicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though many forensic frameworks have been proposed [12,27,11], existing solutions for smart homes give emphasis on acquisition and neglect examination and analysis. Furthermore, no single framework has been acknowledged as superior, due to lack of standardization in IoT and heterogeneity of computer systems [28,29,3].…”
Section: Digital Forensicsmentioning
confidence: 99%
“…In a 2018 report by Symantec regarding the security threats found in the Internet [2], it was reported that the total number of attacks targeting IoT devices for 2018 exceeded 57,000, with more than 5,000 attacks being recorded each month. Hackers have compromised vulnerable, unpatched or unencrypted IoT devices in order to steal sensitive data, corrupt the device's normal operation, spread malware infections [3][4] [2] or even compromise the security of a smart home by disabling smart locks and garage doors [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations